2022
DOI: 10.1186/s12870-022-03665-y
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly of the complete mitochondrial genome of sweet potato (Ipomoea batatas [L.] Lam) revealed the existence of homologous conformations generated by the repeat-mediated recombination

Abstract: Sweet potato (Ipomoea batatas [L.] Lam) is an important food crop, an excellent fodder crop, and a new type of industrial raw material crop. The lack of genomic resources could affect the process of industrialization of sweet potato. Few detailed reports have been completed on the mitochondrial genome of sweet potato. In this research, we sequenced and assembled the mitochondrial genome of sweet potato and investigated its substructure. The mitochondrial genome of sweet potato is 270,304 bp with 23 unique core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 61 publications
4
26
0
Order By: Relevance
“…As an increasing number of mitogenomes are published, studies have found that the size of plant mitogenomes varies greatly, ranging from 66 kb to 11.7 Mb [ 12 , 27 ]. Additionally, studies have revealed that plant mitogenomes differ from chloroplast genomes (always containing the conserved single loop structure) and should be presented in multiple sequence units to show the dynamic connection of the mitogenome [ 3 , 5 , 6 , 28 , 29 ]. The complete mitochondrial genome of Th.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an increasing number of mitogenomes are published, studies have found that the size of plant mitogenomes varies greatly, ranging from 66 kb to 11.7 Mb [ 12 , 27 ]. Additionally, studies have revealed that plant mitogenomes differ from chloroplast genomes (always containing the conserved single loop structure) and should be presented in multiple sequence units to show the dynamic connection of the mitogenome [ 3 , 5 , 6 , 28 , 29 ]. The complete mitochondrial genome of Th.…”
Section: Discussionmentioning
confidence: 99%
“…SSRs and dispersed repeats are important components of repeat sequences in the mitochondrial genome [ 5 , 6 , 8 ]. By comparing the repeat sequences of 7 gymnosperm mitogenomes, it is interesting to find that the number of SSRs in gymnosperms form a definite hierarchy and could well reflect the phylogenetic relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the mitogenome of Populus simonii was assembled into three circular molecules, and all of them had protein-coding capability ( Bi et al., 2022 ). Additionally, the sweet potato ( Ipomoea batatas [L.] Lam) mitogenome was found to have a multicircular structure generated by repeat sequence-mediated recombination ( Yang et al., 2022 ). The mitogenome of plants is much larger than that of other eukaryotes and differs even among related species ( Kubo and Newton, 2008 ; Sloan et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in mitogenome size can be attributed to repetitive sequences and foreign DNA derived from other organisms during evolution [ 9 ]. Many intramolecular recombination events and subgenomic conformations have been found in some land plants, such as Scutellaria tsinyunensis [ 10 ], Cucumis sativus [ 11 ], Ipomoea batatas [ 12 ], and Brassica napus [ 13 ]. In extreme environments, gene loss and RNA edits may occur during plant mitogenome rearrangement [ 14 ].…”
Section: Introductionmentioning
confidence: 99%